The USA’s Ideological Globalism and Ghana’s Religious Frontier Since the 21st Century - Prempeh, Charles (Universitas Islam Indonesia, 2024)
On 26th—29th March, 2023, Kamala Harris, the Vice President (VP) of the United States of America’s leftist party visited Ghana. The visit couched as part of the US seeking to strengthen diplomatic ties with Ghana rather generated the opposite response from the Ghanaian religious constituency. In this article, the author argues that, the US’s VP’s visit was rather read by the country’s overwhelming religious constituency as a decoy on the part of the US to advance its neo-colonial cultural revolution as part of the 21st century globalism. Taking the argument from the beginning of the 21st century, the author maintains that, the utopian idea of the US-dominated world that would foster the end of autocracy and birth economic prosperity has arguably failed. The failure of the vision of globalisation is, as the author argues, because America’s pursuit of ideological politics in support of minority sexual rights runs contrary to the aspiration of family as a religious mandate in the orthodoxy and orthopraxy of Ghana’s religious constituency. Consequently, the author analysing online news report about the backlash that emerged from the US’s VP’s visit concludes that, both Ghana’s President and US VP were involved in making use of the word “we” in direct violation of the terms of the social contract that invest “we” in the people, not the presidents as individuals. Concurrently, compounded by a world reeling under the major disruptions that the coronavirus pandemic caused and the impact of the current impasse between Russia and Ukraine, the author maintains that, America’s cultural and social revolution remains the nemesis of the aspirations of globalisation.